Clinicopathological and surgical comparisons of differentiated thyroid cancer between China and the USA: A multicentered hospital-based study - Zhu, Juan; Sun, Kexin; Wang, Jian; He, Yutong; Li, Daojuan; Liu, Shuzheng; Huang, Yunchao; Zhang, Min; Song, Bingbing; Liao, Xianzhen; Liang, He; Zhang, Qian; et al. (Frontiers in Public Health, 2022)
Background: Thyroid cancer (TC), was the fastest-rising tumor of all malignancies in the world and China, predominantly differentiated thyroid cancer (DTC). However, evidence on TC stage distribution and influencing factors of late-stage were limited in China. Methods: We carried out a retrospective study and enrolled TC patients who were first diagnosed and hospitalized in 8 hospitals in China in 2017. Logistic regression was used to evaluate associations between influencing factors and DTC stage. We extracted eligible primary DTC records newly diagnosed in 2017 from the USA’s Surveillance, Epidemiology, and End Results (SEER) database. We compared clinicopathological features and surgical treatment between our DTC records and those from the SEER database. Results: A total of 1970 eligible patients were included, with 1861 DTC patients with known stage. Among patients ≥ 45 years old, males (OR=1.76, 95%CI 1.17-2.65) and those with new rural cooperative medical scheme insurance (NCMS) (OR=1.99, 95%CI 1.38-2.88) had higher risks of late-stage DTC (stage III-IV). Compared with SEER database, over-diagnosis is more common in China [more DTC patients with onset age< 45 years old (50.3% vs 40.7%, P<0.001), with early-stage (81.2% vs. 76.0%, P<0.001), and with tumors<2cm (74.9% vs. 63.7%, P<0.001)]. Compared with the USA, TC treatment is more conservative in China. The proportion of lobectomy in our database was significantly higher than that in the SEER database (41.3% vs. 17.0%, P<0.001). Conclusions: Unique risk factors are found to be associated with late-stage DTC in China. The differences in the aspect of clinicopathological features and surgical approaches between China and the USA indicate that potential over-diagnosis and over-surgery exist, and disparities on surgery extent may need further consideration. The findings provided references for other countries with similar patterns.